NILAI KETUHANAN SEBAGAI LANDASAN PERBAIKAN KEHIDUPAN BERBANGSA DAN BERNEGARA - Muhammaddin Muhammaddin (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2017)
One of the most fundamental identities of a religion is the divine doctrine or doctrine that recognizes the existence of God. It can even be said is not a religion if there is no main characteristic that is the recognition and confidence of God. Reason alone will honestly acknowledge the power that governs nature and includes human life and reason will refuse if any opinion that says the existence of regularity that occurs in this nature occurs by itself. Because in reality there are natural events that occur is believed not to happen by chance but to the belief may God reprove, angry or indeed happened akiabat causal law from human activities that treat nature unnaturally, to the recognition of God who controls nature and life this. One would think anything of his religion about the process of the creation of man by the meeting of a man and a woman's ovum could be born a man whose system is amazing and an impossible thing to happen by itself if no one created (God) and certainly strengthened from the source of religion especially Islam for example very detailed human procession was created by Allah swt. with its very complete stages described in the holy book of the Qur'an and explained by the Messenger of Allah. as his apostle. All religions teach goodness, both individually, society, life of nation and state. These virtues are called morality and this doctrine is very urgent because goodness based on divine values ​​will be a moral fors ie there is no back door to escape responsibility, if he does immoral or immoral, including wrongdoing, he remains contrary to religious values ​​as well as with state law based on Pancasila and the 1945 Constitution. The divine values ​​teach that people are still guilty of punishment and with sinful sanctions even though their crimes are escaped and escape from the bondage of law convicted by the court for being not discovered by law enforcement apparatus